Factors Associated with Nursing Activities in Humanitarian Aid and Disaster Relief. - Norihito Noguchi; Satoshi Inoue; Chisato Shimanoe; Kaoru Shibayama; Koichi Shinchi (PLoS ONE, 2016)
BACKGROUND:Although nurses play an important role in humanitarian aid and disaster relief (HA/DR), little is known about the nursing activities that are performed in HA/DR. We aimed to clarify the nursing activities performed by Japanese nurses in HA/DR and to examine the factors associated with the frequency of nursing activities. METHODS:A self-administered questionnaire survey was completed by 147 nurses with HA/DR experience. The survey extracted information on demographic characteristics, past experience (e.g., disaster medical training experience, HA/DR experience), circumstances surrounding their dispatched to HA/DR (e.g., team size, disaster type, post-disaster phase, mission term), and the frequency of nursing activities performed under HA/DR. The frequency of nursing activities was rated on a 5-point Likert scale. Evaluation of nursing activities was conducted based on the "nursing activity score", which represents the frequency of each nursing activity. Factors related to the nursing activity score were evaluated by multiple logistic regression analysis. RESULTS:Nurses were involved in 27 nursing activities in HA/DR, 10 of which were performed frequently. On analysis, factors significantly associated with nursing activity score were nursing license as a registered nurse (OR 7.79, 95% CI 2.95-20.57), two or more experiences with disaster medical training (OR 2.90 95%, CI 1.12-7.49) and a post-disaster phase of three weeks or longer (OR 8.77, 95% CI 2.59-29.67). CONCLUSIONS:These results will contribute to the design of evidence-based disaster medical training that improves the quality of nursing activities.